Trajectory of bolt and length of plate in femoral neck system determine the stability of femur neck fracture and risk of subsequent subtrochanteric fracture : a finite element analysis - Jung, Chang Ho; Cha, Yonghan; Chung, Jun Young; Park, Chan Ho; Kim, Tae Young; Yoo, Jun Il; Kim, Jung Taek; Jeon, Yongho (BMC Musculoskeletal Disorders, 2023)
Background: This study aimed to analyze the differences in the stability of fractures, stress distribution around the distal-most screw according to the length of the plate and the trajectory of the bolt in Pauwels type III femoral neck fracture using the femoral neck system (FNS). Methods: Finite element models of Pauwels type III femoral neck fractures were established with surgical variations in the trajectory of the bolt (central, inferior, valgus, and varus) and length of the lateral plate (1- and 2-hole plate). The models were subsequently subjected to normal walking and stair-climbing loads. Results: The screw-holding cortical bone in subtrochanter in the model with a 2-hole plate and the bolt in the inferior trajectory and the models with 1-hole or 2-hole plate and the bolt in valgus trajectory had shown greater maximum principal strain than the models with central or varus trajectories. The gap and sliding distance on the fracture surface were larger with inferior or varus trajectories of the bolt and smaller with the valgus trajectory of the bolt under both loads, compared to those of the central trajectory. Conclusion: For the fixation of Pauwels type III femoral neck fracture, the trajectory of the FNS bolt and the length of the plate affect the mechanical stability of the fracture and the strain of cortical bone around the distal-most screw. The surgical target should stay on the central trajectory of the bolt and the 2-hole plate’s mechanical benefits did not exceed the risk.
Keywords: Biomechanical Phenomena; Femoral Neck Fractures; Femur Neck; Finite Element Analysis; Fracture Fixation, Internal; Hip Fractures; Humans; Bolt trajectory; Femoral neck fractures; Fixation; Pauwels type III